Validation of Modified SOFIT+: Relating Physical Activity Promoting Practices in Physical Education to Moderate-to-vigorous Physical Activity in 5–6 Year Old Children. Issue 4 (2nd October 2021) - Crotti, Matteo; Rudd, James; Weaver, Glenn; Roberts, Simon; O'Callaghan, Laura; Fitton Davies, Katie; Foweather, Lawrence
ABSTRACT: To validate the modified System for Observing Fitness Instruction Time to measure teacher practices related to physical activity promotion (SOFIT+) in physical education (PE) amongst 5–6-year-old-children. Participants ( n = 162, 53% female, 6.0 ± 0.3 yrs) were recruited from 9 schools. Video-recordings of 45 PE lessons from 9 teachers/coaches were coded using a modified SOFIT+. Accelerometers measured children's moderate-to-vigorous physical activity (MVPA). Validity was assessed via multinomial regression measuring the relationship of both SOFIT+ index score and individual teaching practices with children's MVPA. Inter-rater reliability was examined. A 1 unit increase in the SOFIT+ index was associated with increased likelihood to engage in 10–19 sec, 20–29 sec and 30–40 sec of MVPA, compared to 0–10 sec. Most of the observed teaching practices were significantly related to children's MVPA. Inter-rater percentage of agreement ranged between 88.8% and 99.7%. SOFIT+ is a valid and reliable assessment of teaching practices related to MVPA promotion in PE amongst 5–6-year-old-children.